Analisis Pengaruh Bantuan Stimulan Perumahan Swadaya (BSPS) Terhadap Kesejahteraan Masyarakat Berpenghasilan Rendah Di Kabupaten Buru Selatan (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to see the effect of Self-Help Housing Stimulant Assistance (BSPS) on the welfare of low-income people. The data used is primary data obtained from a population of 84 beneficiaries of the self-help housing stimulant assistance program. The analysis method used is multiple linear regression. The results showed that food access and self-help housing stimulant assistance had a positive and significant effect on the welfare of low-income people in South Buru Regency
Keywords: Stimulant, Self-Help, Welfare